Meningkatkan Minat Belajar Siswa Sekolah Dasar melalui Pemanfaatan Literasi Digital Interaktif Berbasis Teknologi - Fatihatuzzahro Fatihatuzzahro; Indri Hertia Rohmah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
The rapid development of digital technology has significantly influenced the educational process, especially in elementary schools. Digital literacy has become an essential skill that supports students in accessing information, understanding learning materials, and participating actively in classroom activities. This study aims to analyze the role of digital literacy in increasing students’ learning interest in elementary school education. The research employed a qualitative descriptive method using observation, interviews, and literature studies as data collection techniques. The findings indicate that the implementation of digital-based learning media, such as educational videos, interactive quizzes, online learning platforms, and digital applications, can create a more engaging and enjoyable learning atmosphere for students. In addition, digital literacy encourages students to learn independently, improve critical thinking skills, and enhance creativity during the learning process. Teachers also play an important role in guiding students to use technology wisely, responsibly, and effectively in educational activities. The use of digital literacy in learning activities helps reduce boredom and increases students’ enthusiasm and participation in the classroom. Furthermore, technology-based learning enables students to access broader learning resources beyond textbooks. Therefore, the integration of digital literacy into elementary education can be considered an effective strategy to improve students’ learning interest and learning quality in the modern digital era.